Pengaruh pesan gizi singkat dan pendidikan gizi terhadap praktik makan pasien rawat inap di Rumah Sakit Umum Daerah Salatiga - Simanjuntak, Rohani Retnauli; Kartasurya, Martha Irene; Rosidi, Ali (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2016)
Background : the low dietary intake in hospitalized patients impact on low level of energy and protein adequacy. Short nutritional message and nutrition education could influence the patient’s eating practice in order to increase score of knowledge, attitude, level of energy and protein adequacy.Objective : to analyze the effects of short nutritional message and nutrition education on eating practice in hospitalized patients at Salatiga general hospital.Method : this was a quasi experimental study with control group pre-test post-test design. The treatment group (38 respondents) received hospital food (3 days) and nutritional short message and education nutrition from the nutritionist (2 days), meanwhile the control group (38 respondents) received hospital food (3 days) only. Score of knowledge and attitude were obtained from interview with questioner. Energy and protein adequacy level come from hospital food intake and recall.Results : there were no differences in nutritional knowledge score, attitude, protein and energy adequacy level before intervention in both group. Score of knowledge, attitude, level of energy and protein adequacy could be increased by short nutritional message and nutrition education (p=0,00, p=0,00, p=0,00, dan p=0,00). Short nutritional message and nutrition education was no effect on energy and protein adequacy level from food outside hospital (p=0,76 and p =0,86).Conclusion: Short nutritional message and nutrition education was increasing nutritional knowledge and attitude score, energy and protein adequacy level from hospital food and total intake.